THE FREE PUBLIC RECORDS AS A FUNDAMENTAL CONDITION FOR THE EXERCISE OF CITIZENSHIP AND FUNDAMENTAL RIGHTS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The article analyzes the phenomenon of gratuities in public records, considering it as a public policy implemented by the State in order to promote the necessary conditions for the exercise of citizenship, in order to make it a tangible reality. It is understood from the doctrine and jurisprudence that the notary and registration services are public services remunerated by rate, which is fixed by state law. The article 236 of the Federal Constitution, in disciplining the notary and registration services, confers on the Federal Government the power to legislate on general norms on emoluments, which was done by the edition of Law 10.169/2000, and it is the responsibility of the States to establish their fees based on regional interests. It occurs that Federal Law 9.534/97, amended Law 6.015/73 and extended the list of gratuities of the acts practiced by the Registry of Natural Persons in addition to the immunities provided for in article 5, LXXVIII, which, in the first instance, would configure exemption. In the same sense are the gratuities provided in the law that deals with land regularization. The Federal Supreme Court, when expressing its views on the former, dismissed the injunction that sought the suspension of the effects of federal law because it considered the importance of acts performed by the Civil Registry to promote citizenship, especially birth registration, which serves as a basis for obtaining other citizen documents. The research was guided by the deductive method, and was based on books, scientific articles, legislation and jurisprudence, as well as on specialized publications.